Human phase‐I metabolism and prevalence of two synthetic cannabinoids bearing an ethyl ester moiety: 5F‐EDMB‐PICA and EDMB‐PINACA. Issue 3 (24th November 2022) - Giorgetti, Arianna; Brunetti, Pietro; Haschimi, Belal; Busardò, Francesco Paolo; Pelotti, Susi; Auwärter, Volker
Abstract: Around 2017, with the appearance of 5F‐EDMB‐PINACA, synthetic cannabinoids (SCs) carrying an ethyl ester moiety at the linked group started spreading on the market of new psychoactive substances (NPS). In 2020 and 2021, the indole analog of 5F‐EDMB‐PINACA (5F‐EDMB‐PICA) and the non‐fluorinated analog of this compound (EDMB‐PINACA) were analytically characterized. Here, we present suitable urinary markers to prove the consumption of these two ethyl analogs. Ten authentic urine samples for each compound were analyzed by liquid chromatography–quadrupole time‐of‐flight mass spectrometry (LC‐qToF‐MS). Anticipated phase‐I metabolites detected in urine samples were confirmed in vitro by applying a pooled human liver microsomes (pHLM) assay. Prevalence data were obtained from urines collected for abstinence control and submitted to a screening method for SC metabolites. Ten phase‐I metabolites of 5F‐EDMB‐PICA and 18 of EDMB‐PINACA were detected by LC‐qToF‐MS analysis of authentic urine specimens. The main in‐vivo metabolites were built by ester hydrolysis, often coupled to further metabolic processes. Investigation of phase‐I biotransformation led to the identification of ester hydrolysis, monohydroxylation, and defluorination products as the most suitable urinary biomarkers for 5F‐EDMB‐PICA. Metabolites formed by ester hydrolysis coupled to ketone formation and by monohydroxylation are suggested for the detection of EDMB‐PINACA. From October 1, 2020 to February 1, 2022, among positive urine samples, 5.4% and 10.1% tested positive 5F‐EDMB‐PICA and EDMB‐PINACA, respectively. Due to common metabolites shared among structurally related SCs, the unequivocal detection of their consumption remains challenging for forensic laboratories and requires sensitive methods to monitor multiple metabolites, ideally including highly specific species. Abstract : The unequivocal detection of 5F‐EDMB‐PICA and EDMB‐PINACA consumption requires sensitive methods to monitor multiple urinary biometabolites.